Persebaran Potensi Cagar Budaya Megalithikum di Kabupaten Poso Sulawesi Tengah - Haliadi, Haliadi; Butudoka, Zubair; Djorimi, Iksam (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2024)
The Governor of Central Sulawesi has declared that Central Sulawesi Province will have a thousand megaliths on October 10 2023 because it has the potential for Cultural Heritage (CH) in the form of megalithic stones as evidence of civilization in the Central Sulawesi Region, especially in Poso Regency. This article will focus on three valleys in Poso Regency, namely the Bada Valley, Behoa Valley and Napu Valley. The research entitled